SAT0187 DISCRIMINATION OF SYSTEMIC LUPUS (SLE) PATIENTS WITH CLINICAL RESPONSE TO OBEXELIMAB (XMAB®5871) BASED ON A PATTERN OF IMMUNOLOGIC MARKERS. (2nd June 2020) - Merrill, J. T.; Guthridge, J.; Zack, D.; Foster, P.; Burington, B.; Tran, L.; Smith, M.; James, J. A.
Abstract : Background: We recently reported Phase 2 SLE trial results of obexelimab, an FcγRIIb agonist (suppressor of B cell activation). Obexelimab did not meet the primary endpoint (% of patients without flare at Day 225) (p=0.183) but other endpoints such as time to flare (p=0.025) were met. Objectives: 1. To assign SLE patients to phenotypic subsets based on patterns of gene expression in immune-related pathways. 1 2. To explore the association of immune patterns and clinical response to obexelimab. Methods: This analysis included 71 of the 104 participants in the obexelimab study, those who either completed the protocol or terminated for disease flare, if there were adequate blood samples (biomarker subset). At screening, patients were assigned to clusters based on 41 SLE co-expression signature modules from the Human Immune Phenotyping Consortium via unsupervised random forest and K-means clustering. 2 Other markers of SLE disease were also examined. The BOLD 3 study design mandated withdrawal of background immunosuppressants, supporting less ambiguous pharmacodynamic analysis as the trial progressed. Results: Immune pathway expression patterns of 7 patient clusters (Fig 1a ) confirmed our prior characterization of 200 non-overlapping SLE patients. 2 The biomarker subset retained a trend of longer time to first flare in patients receiving obexelimab (n=38) vs placebo (n=33) (Fig1b, HR 0.61, p=0.11). A smaller set of only Clusters 3 and 6 demonstrated marked increased time to flare in the obexelimab group (n=13) compared to placebo (n=14) (Fig 1c, HR 0.22, p=0.025). Obexelimab had no effect on other clusters (Fig 1d ). The responder clusters shared low expression of inflammation modules (p < 0.001) compared to other clusters and high expression of T Cell, immune response, cell cycle, mitochondrial modules (all p < 0.001) and B Cell modules (p=0.006). We therefore sorted patients by these specific features regardless of cluster assignment. Figure 2 shows significant impact of obexelimab on time to flare in 64 patients with B Cell pathway activation (HR 0.5, p=0.038), although less robust by itself than found in Clusters 3 and 6. In a group with high B or plasma cell modules but low inflammation (n=46), treatment effect increased (HR 0.35, p=0.019). Between Screening and Baseline, as brief steroids were given and background treatments withdrawn, expression of B Cell and Plasma Cell pathways increased. Both then decreased after treatment with obexelimab but not placebo (p< 0.0001 and p< 0.001 respectively), an effect not seen with other immune pathway modules. Conclusion: Precision medicine for SLE has been hampered by heterogenous immune signals with variable expression. Clustering of patients by gene co-expression pathways enabled an efficient, hierarchical array that reduplicated results of a prior SLE cohort, suggesting these are not random phenotypes. Of these 7 reproducible SLE subsets, the combination of clusters 3 and 6 distinguished an obexelimab responder population of 27 out of 71 subjects (38%) with high expression of B and T Cell modules and cell activation pathways. Focus on the defining features shared by these clusters revealed specific factors associated with response, enabling inclusion of some patients from other clusters in an optimized responder population of 46/71 (65% of subjects). B Cell and Plasma Cell pathways demonstrated mechanism-related pharmacodynamic effects of obexelimab. Lack of responders with high expression of inflammation modules could implicate inhibitory factors to obexelimab within inflammatory pathways, potentially targetable by complementary treatments. References: [1]Banchereau Cell 165:1548 2016 [2]Lu ACR Abstract #2977 2017 [3]Merrill Arthritis Rheumatol 69: 1257 2017 Disclosure of Interests: Joan T Merrill Grant/research support from: Xencor, Bristol Myers Squibb, Glaxo Smith Kline, Consultant of: Xencor, Abbvie, UCB, Glaxo Smith Kline, EMD Serono, Astellas, Remegen, Celgene/Bristol Myers Squibb, Exagen, Astra Zeneca, Amgen, Jannsen, Servier, ILTOO, Daitchi Sankyo, Lilly, Paid instructor for: Abbvie, Bristol Myers Squibb, Joel Guthridge Grant/research support from: Xencor, Bristol Myers Squibb, DXterity, Debra Zack Shareholder of: Xencor, Employee of: Xencor, Paul Foster Shareholder of: Xencor Inc, Employee of: Xencor Inc, Bart Burington Shareholder of: Xencor Inc, Employee of: Xencor Inc, Ly Tran: None declared, Miles Smith: None declared, Judith A. James Grant/research support from: Progentec Diagnostics, Inc, Consultant of: Abbvie, Novartis, Jannsen